A SOSIALISASI PENGGUNAAN SISTEM INFORMASI GURU BIMBINGAN KONSELING(BK) BERBASIS WEBSITE: SOSIALISASI PENGGUNAAN SISTEM INFORMASI GURU BIMBINGAN KONSELING(BK) BERBASIS WEBSITE - AKHMAD SAYUTI AKHMAD (Abdi Reksa, 2024)
Information system needs cover almost all areas of life. Accurate, fast and relevant information is needed in organizations. However, in reality, due to the lack or limited use of information systems, it is sometimes out of sync with the wishes and expectations to be realized. Bina Sriwijaya Vocational School is a school majoring in Office Administration, Computer Accounting, Computer Network Engineering, Hospitality Accommodation that needs to develop information technology that can use the Website for communication between students, Counseling Teachers and parents. The reporting system for student violations at schools is currently still done manually or offline so that parents and Counseling Guidance teachers still find it difficult to follow up on every student's customer. Community service activities are carried out to provide assistance to students, website operators, Counseling teachers and representatives of parents for the use of a Website-Based Information System so that it can be used anytime and anywhere.